Multivalent Glycosheets for Double Light–Driven Therapy of Multidrug‐Resistant Bacteria on Wounds - Hu, Xi‐Le; Chu, Linyang; Dong, Xiaojing; Chen, Guo‐Rong; Tang, Tingting; Chen, Daijie; He, Xiao‐Peng; Tian, He (Advanced functional materials, 2019)
With the evergrowing threat posed by multidrug resistance of bacteria, the development of effective antibacterial agents remains a global challenge. Infection with multidrug‐resistant bacteria in hospitals significantly impairs the healing of wounds caused by deep‐burn injuries or diabetic foot ulceration, leading to a high mortality rate among these patients. A multivalent glycosheet for the double light–driven therapy against multidrug‐resistant Pseudomonas aeruginosa (P. aeruginosa) infection on wounds is developed here. Galactose‐ and fucose‐based ligands are self‐assembled to form a glyco‐layer on the surface of thin‐layer molybdenum disulfide, producing the glycosheets capable of selectively localizing P. aeruginosa through multivalent carbohydrate–lectin interactions. The glycosheets loaded with antibiotics have proven applicable for: 1) near‐infrared‐light driven, in situ thermal release of antibiotics, increasing bacterial membrane permeability, and 2) white light–driven reactive‐oxygen‐species production to more thoroughly kill the bacteria. The targetability, together with the light sensibility, of the glycosheets enables a highly effective and optically controlled therapeutic regime for the healing of wounds infected by multidrug‐resistant as well as clinically isolated P. aeruginosa. A multivalent, double light–driven glycosheet is developed for the effective killing of multidrug‐resistant, clinically isolated P. Aeruginosa on wounds.